Tripartite motif-containing protein 50 suppresses triple-negative breast cancer progression by regulating the epithelial–mesenchymal transition - Danxiang Chen; Jing Jiang; Wei Zhang; Xinlin Li; Qidong Ge; Xia Liu; Xujun Li (Cancer Biology & Therapy, 2024)
Background and Objectives Tripartite motif-containing protein 50 (TRIM50) is a recently discovered E3 ubiquitin ligase that participates in tumor progression. TRIM50 is overexpressed in many cancers, although few studies focused on TRIM50‘s role in breast cancer.Methods We overexpressed TRIM50 in triple-negative breast cancer cell lines using plasmid and found that TRIM50 upregulation markedly reduced breast cancer cell proliferation, clone formation, and migration, as well as promoted breast cancer cell apoptosis. Western blotting revealed that accumulated TRIM50 resulted in both mRNA and protein depletion of SNAI1, and partially attenuated the epithelial–mesenchymal transition (EMT) induced by SNAI1.Results In this study, we demonstrate that TRIM50 is downregulated in human breast cancer and that its overexpression closely correlates with diminished invasion capacity in breast cancer, suggesting that TRIM50 may serve as a diagnostic marker and therapeutic target.Conclusion TRIM50 plays a key role in breast cancer proliferation and potentially serves as a prognostic and therapeutic target.